Transportation Modeling in Supporting Sustainable Transportation Systems and Low Emission Zone Planning Development in Indonesian Tourism Destinations - Efendhi Prih Raharjo; Annisa Mahadita Candrarahayu; Febrianto Fatah Yogatama; I Kadek Surya Putra Adidana (Jurnal Teknologi Transportasi dan Logistik, 2022)
Sustainable areas are currently needed in the development of tourism destinations. A sustainable transportation system and the urgency of environmental sustainability are one of the main supporting aspects in achieving regional sustainability. This research aims to produce transportation modeling in support of sustainable transportation systems and the development of Low Emission Zone planning in tourism destinations. The method used in this study is a quantitative method developed through transportation modeling using the Vissim and Visum programs. The analysis was carried out on roads in the Ubud Bali Tourism Area. The results of transportation modeling show that sustainable transportation system planning can reduce the impact of tourism on the transportation sector and the environment by increasing the level of service to A and resulting in reduced air pollution as a result of implementing the Low Emission Zone area.